Hypertension clinic drug choices: tips for pharmacist prescribers. Issue 7 (22nd July 2019) - Girvin, Briegeen
Abstract : In the second of our two‐part series on helping pharmacist independent prescribers set up and run a hypertension clinic in primary care, Briegeen Girvin discusses the factors to consider when prescribing and monitoring antihypertensive drugs and statins.